Shopping with Voice Assistant: Understanding Consumer Intention and the Mediating Role of Trust - Kumar, Naveen; Singh, Vasundhra (Indian Journal of Marketing, 2022)
Voice assistants are a new smart tool in the market to assist and ease the shopping process for consumers. A voice assistant, along with its in-built artificial intelligence, makes consumer and device interaction more humanlike and personal. Despite a promising debut in the Indian market, there has been limited research on the Indian consumers’ intention to use VA for online shopping. Most of the studies are exploratory in nature and lack a clear theoretical framework. This study aimed to tap the growing trend of the use of voice assistants in the Indian market. The study focused on finding what factors determine consumer intention to shop online using a voice assistant. How does trust upon a voice assistant affect the relationship between these factors and intention? This is a cross-sectional quantitative study. A convenience sample of 121 respondents participated in the study using an online structured questionnaire. The hypotheses testing was done using AMOS SEM. The tests confirmed that information quality and system quality impacted intention only when mediated through trust. Interaction quality, however, only had a direct effect, and no mediation through trust was determined. The study explained how more sincere efforts by VA in information searching and delivering the right information to consumers lead to the development of trust in the VA.